Hubungan Antara Kecepatan Lari, Kelentukan dan Daya Ledak Tungkai Dengan Kemampuan Lompat Jauh Murid SD Negeri Karuwisi 1 Makassar - ZAINUDDIN, FADLI (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
This research Â is a descriptive Â research using correlation al Â research Â design. ThisÂ Â Â study aimsÂ Â Â to determine; Â (1) Â Is thereÂ any relationshipÂ Â Â between Â running Â speedÂ Â Â and longÂ Â Â jump Â abilityÂ Â Â Â Â Â Â of elementaryÂ school students Â of Karuwisi Â 1 Makassar Â State;Â Â Â (2) IsÂ Â Â thereÂ Â Â a correlation Â between Flexibility and Long Jump abilityÂ Â Â Â of elementary school students of Karuwisi 1 Makassar State ; (3) Is there a correlationÂ between the explosive powerÂ Â of theÂ Â limbs withÂ Â the longÂ Â jump abilityÂ Â of elementary school students of Karuwisi 1 Makassar State; Â (4) Is Â there any relation between running speed, Flexibility and explosive limb Â power with Â long jump abilityÂ Â Â Â of elementary school students of Karuwisi 1 Makassar State. Its population is all students of SD Negeri 1 Karuwisi Makassar. The samples used are male students as many as 30 people. The simple determination Â technique Â is by random selection by drawing (Simple Random Sampling). Data analysis technique used is descriptive analysis, Pearson product moment (r) correlation coefficient analysis, regression analysis and multiple correlation analysis (R) through SPSS 15 program at significant level Î±, 0,05. The results showed that; (1) There is a significant relationship Â between running speed and long jump ability of elementary school students of KaruwisiÂ 1 Makassar, Â with r value of -0.653 (Pvalue <a 0.05); (2) There is a significant correlation between determination with long jump ability of elementary school students of Karuwisi 1 Makassar, with r value of 0.663 (Pvalue <a 0.05); (3) There is a significant correlation between limb power and long jump ability of elementary school students Karuwisi 1 Makassar, with r value of 0,733 Pvalue <a 0,05); (4) There is a significant relation between running speed, Flexibility, and limb power with long jump ability of elementary school students of Karuwisi 1 Makassar, with Ro value 0,866 (Pvalue <a 0,05).